The Influence of Artificial Intelligence Integration, Customer Technology Proficiency, Innovation Culture on E-Commerce Adoption and Its Impact on Marketing Performance With Entrepreneurial Orientation as a Moderation Variable - Kurniawan, Andy; Prihandono, Dorojatun (Devotion : Journal of Research and Community Service, 2025)
This research is motivated by the low level of e-commerce adoption among Kendal's MSMEs, despite the government's implementation of various initiatives to support digital transformation. This study aims to analyze the influence of artificial intelligence integration, customer technological skills, and a culture of innovation on e-commerce adoption and its impact on marketing performance, with entrepreneurial orientation as a moderating variable. The sampling technique used in this study was a non-probability sampling method, namely purposive sampling, using primary data sources. The population included all MSMEs in Kendal. The sample consisted of 300 respondents, all MSMEs in Kendal. Data collection was conducted using an online questionnaire via Google Forms. Data processing used Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that AI integration had a positive and significant effect on marketing performance for MSMEs in Kendal Regency. AI integration has a positive and significant effect on E-commerce Adoption for MSMEs in Kendal Regency. Customer Technology Savviness has a positive (0.948) and significant effect on Marketing Performance for MSMEs in Kendal Regency. Customer Technology Savviness has a positive and significant effect on E-commerce Adoption for MSMEs in Kendal Regency. Innovation Culture has a positive and significant effect on Marketing Performance for MSMEs in Kendal Regency. Innovation Culture has a positive and significant effect on E-commerce Adoption for MSMEs in Kendal Regency. E-commerce adoption has a positive and significant effect on marketing performance for MSMEs in Kendal Regency. Entrepreneurial orientation moderates the strengthening relationship between e-commerce adoption and MSME marketing and is significant.